A1.24 Cilengitide reduces pannus formation and bone erosions in collagen induced arthritis. (31st January 2014) - Sykoutri, D; Geetha, N; Hayer, S; Mandl, P; Chilla, A; Smolen, J; Prager, G; Redlich, K
Abstract : Background and Objectives: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterised by synovial inflammation and osteoclast (OC) mediated bone erosions. AlphaVbeta3 integrin (αvβ3) is highly expressed in OCs and αvβ3 blocking antibodies reduce bone resorption. We have shown that Cilengitide, a synthetic Arginine-Glycine-Asparagine peptide (RGD-peptide), effectively inhibits osteoclastogenesis in vitro and reduces clinical signs of arthritis in Collagen Induced Arthritis (CIA). We aimed to further characterise the effect of cilengitide in arthritis. Materials and Methods: CIA was induced in 6-8 week old male DBA/1 mice by immunisation with bovine type II collagen (CII) at day 1 and boosting at day 21. For CIA prevention mice received 1.5 mg/kg cilengitide (n = 15) or placebo (n = 15) subcutaneously (s.c.), 5 days/week, starting 1 day prior to CIA induction until day 53. For CIA treatment mice with established arthritis were randomised and received 1.5 mg/kg (low dose) or 75mg/kg (high dose) cilengitide or placebo s.c. 5 days/week until day 59. Incidence and severity of arthritis was assessed by weekly clinical scoring of paw swelling and grip strength. In the end histological staining was performed on hind paws with haematoxylin and eosin (H&E) for quantification of pannus, tartrate-resistant acid phosphatase (TRAP) for detection of bone erosions and OCs, toluidine blue (TB) for determination of cartilage breakdown. Blood vessel formation was assessed with endomucin staining. Cellular composition of joint infiltrates was determined with immunohistochemistry with anti-CD3, CD45RO, F4/80 and Neutrophil 7/4 antibodies. Results: In the preventive experiment, cilengitide significantly reduced incidence (92.8% vs. 40%) and severity of CIA. Histological examination revealed significantly reduced numbers of synovial OCs, extent of bone destruction, cartilage damage as well as reduction of inflammatory pannus formation. In addition, blood vessel density in pannus was significantly reduced. Similarly, in the treatment experiment, low and high dose cilengitide effectively inhibited progression of established arthritis as evidenced by amelioration of clinical disease activity scores and histopathology. Conclusions: Our findings demonstrate that cilengitide potently prevents and treats experimental CIA, reducing osteoclast-mediated bone erosions and inflammation. Further investigation of its mechanism of action in arthritis, in respect to neovascularisation and osteoclast function, may optimise its effect and provide a novel therapeutic target in RA.